2008
DOI: 10.1016/j.juro.2007.10.078
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Ultrasound Evaluation of Dysfunctional Voiding in Women With Recurrent Urinary Tract Infections

Abstract: We think that perineal ultrasound is useful in the evaluation of dysfunctional voiding in women with recurrent urinary tract infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 19 publications
1
37
1
Order By: Relevance
“…Urethral sphincter volume was measured using a 7.5 MHz transvaginal ultrasound probe, where volume was calculated using formula for the volume of a cylinder, as described (Kondo et al, 2001;Wiseman et al, 2002). We observed that maximum urethral sphincter volume was significantly increased in patients with recurrent UTIs and dysfunctional voiding (2.87+0.41 cm 3 ) compared to patients with recurrent UTIs and normal perineal activity during voiding and to control patients (1.77+0.62 cm3 and 1.61+0.32 cm 3 respectively); abnormal findings at ultrasound included thickening of individual rings, haziness of contours and change in echogenic texture with loss of the characteristic four-rings appearance; these findings were observed only in patients with dysfunctional voiding (Minardi et al, 2008). Detrusor wall thickness as assessed by suprapubic ultrasound ranged from 2.2 to 9.3 mm.…”
Section: Ultrasoundmentioning
confidence: 91%
See 4 more Smart Citations
“…Urethral sphincter volume was measured using a 7.5 MHz transvaginal ultrasound probe, where volume was calculated using formula for the volume of a cylinder, as described (Kondo et al, 2001;Wiseman et al, 2002). We observed that maximum urethral sphincter volume was significantly increased in patients with recurrent UTIs and dysfunctional voiding (2.87+0.41 cm 3 ) compared to patients with recurrent UTIs and normal perineal activity during voiding and to control patients (1.77+0.62 cm3 and 1.61+0.32 cm 3 respectively); abnormal findings at ultrasound included thickening of individual rings, haziness of contours and change in echogenic texture with loss of the characteristic four-rings appearance; these findings were observed only in patients with dysfunctional voiding (Minardi et al, 2008). Detrusor wall thickness as assessed by suprapubic ultrasound ranged from 2.2 to 9.3 mm.…”
Section: Ultrasoundmentioning
confidence: 91%
“…Sudden variations in the urethral pressure during bladder filling in people affected by DV were demonstrated, represented by pressure decreases with short periods of electromyography silence, intermittent urethral pressure increases with short perineal spasms, or urethral pressure decreases with silent electromyography, combined with different degrees of bladder instability (Vereecken & Proesmans, 2000). Furthermore, some degree of external sphincter hypertrophia was noted in some studies conducted on females affected from dysfunctional voiding and a positive correlation between dysfunctional behaviors and sphincter volume postulated (Minardi et al, 2008). Its role in the pathogenesis is, anyway, still to be determined.…”
Section: Pathophysiology Of Dysfunctional Voidingmentioning
confidence: 98%
See 3 more Smart Citations